Diagnostic and Prognostic Biomarkers of Adrenal Cortical Carcinoma. (February 2018) - Mete, Ozgur; Gucer, Hasan; Kefeli, Mehmet; Asa, Sylvia L.
Abstract : The diagnosis of low-grade adrenal cortical carcinoma (ACC) confined to the adrenal gland can be challenging. Although there are diagnostic and prognostic molecular tests for ACC, they remain largely unutilized. We examined the diagnostic and prognostic value of altered reticulin framework and the immunoprofile of biomarkers including IGF-2, proteins involved in cell proliferation and mitotic spindle regulation (Ki67, p53, BUB1B, HURP, NEK2), DNA damage repair (PBK, γ-H2AX), telomere regulation (DAX, ATRX), wnt-signaling pathway (beta-catenin) and PI3K signaling pathway (PTEN, phospho-mTOR) in a tissue microarray of 50 adenomas and 43 carcinomas that were characterized for angioinvasion as defined by strict criteria, Weiss score, and mitotic rate–based tumor grade. IGF-2 and proteins involved in cell proliferation and mitotic spindle regulation (Ki67, p53, BUB1B, HURP, NEK2), DNA damage proteins (PBK, γ-H2AX), regulators of telomeres (DAXX, ATRX), and beta-catenin revealed characteristic expression profiles enabling the distinction of carcinomas from adenomas. Not all biomarkers were informative in all carcinomas. IGF-2 was the most useful biomarker of malignancy irrespective of tumor grade and cytomorphologic features, as juxtanuclear Golgi-pattern IGF-2 reactivity optimized for high specificity was identified in up to 80% of carcinomas and in no adenomas. Loss rather than qualitative alterations of the reticulin framework yielded statistical difference between carcinoma and adenoma. Angioinvasion defined as tumor cells invading through a vessel wall and intravascular tumor cells admixed with thrombus proved to be the best prognostic parameter, predicting adverse outcome in the entire cohort as well as within low-grade ACCs. Low mitotic tumor grade, Weiss score, global loss of DAXX expression, and high phospho-mTOR expression correlated with disease-free survival, but Weiss score and biomarkers failed to predict adverse outcome in low-grade disease. Our results underscore the importance of careful morphologic assessment coupled with ancillary diagnostic and prognostic biomarkers of ACC.